2006
DOI: 10.1007/s10532-005-9029-3
|View full text |Cite
|
Sign up to set email alerts
|

Biostimulation for the Treatment of an oil-contaminated Coastal Salt Marsh

Abstract: A field study was conducted on a coastal salt marsh in Nova Scotia, Canada, during the summer of 2000. The objective of the study was to assess the effectiveness of biostimulation in restoring an oil-contaminated coastal marsh dominated by Spartina alterniflora under north-temperate conditions. Three remediation treatments were tested with two additional unoiled treatments, with and without added nutrients, serving as controls. This research determined the effectiveness of nitrogen and phosphorus addition for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 26 publications
1
25
2
2
Order By: Relevance
“…Hirschorn et al (2007) have reported based on stable carbon isotope analysis that the dechlorination of TCE was occurring in in situ biostimulation pilot test areas during biostimulation. Garcia-Blanco et al (2007) have assessed the effectiveness of biostimulation in restoring an oil-contaminated coastal marsh dominated by Spartina alterniflora under north-temperate conditions through nitrogen and phosphorus addition for accelerating oil disappearance, and then have equally determined the role of nutrients in enhancing restoration in the absence of wetland plants, and the rate at which the stressed salt marsh recovered. It was reported that GC-MS resolved alkanes and aromatics degraded substantially ([90 and [80%, respectively) after 20 weeks with no loss of TPH.…”
Section: Biostimulationmentioning
confidence: 99%
“…Hirschorn et al (2007) have reported based on stable carbon isotope analysis that the dechlorination of TCE was occurring in in situ biostimulation pilot test areas during biostimulation. Garcia-Blanco et al (2007) have assessed the effectiveness of biostimulation in restoring an oil-contaminated coastal marsh dominated by Spartina alterniflora under north-temperate conditions through nitrogen and phosphorus addition for accelerating oil disappearance, and then have equally determined the role of nutrients in enhancing restoration in the absence of wetland plants, and the rate at which the stressed salt marsh recovered. It was reported that GC-MS resolved alkanes and aromatics degraded substantially ([90 and [80%, respectively) after 20 weeks with no loss of TPH.…”
Section: Biostimulationmentioning
confidence: 99%
“…Only a very few studies have compared microbial petroleum hydrocarbon degradation in vegetated versus non-vegetated marine and salt marsh sediments in the lab (Wright et al 1997(Wright et al , 2004Launen et al 2002) or the field (Garcia-Blanco et al 2007) and with the exception of the studies conducted by Daane et al (2001Daane et al ( , 2002 none have characterized the specific PAH-degrading microbial communities present in Spartina-dominated petroleum impacted salt marshes.…”
Section: Introductionmentioning
confidence: 99%
“…In a study to determine the effi ciency of biostimulation in restoring oil-contaminated coastal marsh dominated by Spartina alternifl ora through the addition of phosphorous and nitrogen under temperate condition, Garcia-Blanco et al ( 2007 ) reported that >80-90 % oil disappeared after 20 weeks. Biostimulation of a petroleum spilled site was successful in Bellingham, Washington when the activity and population of sulphur-reducing bacteria such as Desulfobacter sp.…”
Section: In-situ Remediation Approaches For the Management Of Contamimentioning
confidence: 99%